Application of primary healthcare principles in national community health worker programmes in low-income and middle-income countries: a scoping review. Issue 2 (2nd February 2022) - Perveen, Shagufta; Lassi, Zohra S; Mahmood, Mohammad Afzal; Perry, Henry B; Laurence, Caroline
Abstract : Objective: To identify which primary healthcare (PHC) principles are reflected in the implementation of national community health worker (CHW) programmes and how they may contribute to the outcomes of these programmes in the context of low-income and middle-income countries (LMICs). Design: Scoping review. Data sources: A systematic search was conducted through PubMed, CINAHL, EMBASE and Scopus databases. Eligibility criteria: The review considered published primary studies on national programmes, projects or initiatives using the services of CHWs in LMICs focused on maternal and child health. We included only English language studies. Excluded were programmes operated by non-government organisations, study protocols, reviews, commentaries, opinion papers, editorials and conference proceedings. Data extraction and synthesis: We reviewed the application of four PHC principles (universal health coverage, community participation, intersectoral coordination and appropriateness) in the CHW programme's objectives, implementation and stated outcomes. Data extraction was undertaken systematically in an excel spreadsheet while the findings were synthesised in a narrative manner. The quality appraisal of the selected studies was not performed in this scoping review. Results: From 1280 papers published between 1983 and 2019, 26 met the inclusion criteria. These 26 papers included 14 CHW programmes from 13 LMICs. Universal health coverage and community participation were the two commonly reported PHC principles, while intersectoral coordination was generally missing. Similarly, the cultural acceptability aspect of the principle of appropriateness was present in all programmes as these programmes select CHWs from within the communities. Other aspects, particularly effectiveness, were not evident. Conclusion: The implementation of PHC principles across national CHW programmes in LMICs is patchy. For comprehensiveness and improved health outcomes, programmes need to incorporate all attributes of PHC principles. Future research may focus on how to incorporate more attributes of PHC principles while implementing national CHW programmes in LMICs. Better documentation and publications of CHW programme implementation are also needed.